Phylogenetic relationships within Turneraceae based on morphological characters with emphasis on seed micromorphology - Arbo, Maria Mercedes (2015)
Genera of Turneraceae differ notably in connation/adnation of calyx, corolla, and androecium. Floral and seed morphology were analyzed in all genera. Phylogenetic analyses were made using a matrix of 91 characters coded for 102 taxa including all genera of Turneraceae and all series of Turnera. Our goals were: assessing the impact of morphology in the cladistic analyses of Turneraceae and comparing our results with those based on molecular datasets. Our analyses suggest that all genera are monophyletic. The inclusion of seed micromorphology in the analyses increased resolution within Turnera, the strict consensus tree shows four main clades, each gathering two or more current series. A comparison of morphological and molecular trees is difficult to make due to the great differences in taxon sampling. However, some clades or subclades are consistent in both phylogenetic approaches. Apparently, the formation of a floral tube conferred an evolutionary advantage to the Turneraceae, because it developed in 66 % of the genera. The morphological complexity of the tube increased in several steps: (1) adnation of petal claws to calyx, developing a perianth tube; (2) partial adnation of stamens to the perianth tube; (3) fusion of sepal and petal veins, shaping a 10-veined perianth tube; (4) development of nectar pockets up to the throat turning the tube into an appendicular hypanthium. The reddish-orange aril, associated with ornitochory, is plesiomorphic in Turneraceae, represented only in Erblichia; the other genera have white/whitish aril, associated with mirmecochory, except Mathurina, with an aril divided into filaments as an adaptation to anemochory.